Effects of alfaxalone, propofol and isoflurane on cerebral blood flow and cerebrovascular reactivity to carbon dioxide in dogs: A pilot study. (January 2023) - Bini, G.; Bailey, K.M.; Voyvodic, J.T.; Chiavaccini, L.; Munana, K.R.; Keenihan, E.K.
Abstract: Propofol total intravenous anesthesia is a common choice to anesthetize patients with increased intracranial pressure, reducing cerebral blood flow while maintaining cerebrovascular reactivity to CO2 . Propofol and alfaxalone are commonly used for total intravenous anesthesia in dogs, but the effects of alfaxalone on cerebral blood flow and cerebrovascular reactivity to CO2 are unknown. Our hypothesis was that alfaxalone would not be significantly different to propofol, while isoflurane would increase cerebral blood flow and decrease cerebrovascular reactivity to CO2 . Six healthy hound dogs were evaluated in this randomized crossover trial. Dogs were anesthetized with 7.5 mg/kg propofol, 3 mg/kg alfaxalone or 8 % sevoflurane, mechanically ventilated and maintained with propofol (400 µg/kg/min), alfaxalone (150 µg/kg/min) or 1.7 % end-tidal isoflurane, respectively, with one week washout between treatments. Cerebral blood flow and cerebrovascular reactivity to CO2 during hypercapnic and hypocapnic challenges were measured using arterial spin labelling and blood oxygen level-dependent magnetic resonance imaging sequences, respectively. Median (interquartile range, IQR) normocapnic cerebral blood flow was significantly lower ( P = 0.016) with alfaxalone compared to isoflurane, in the whole brain 15.39 mL/min/100 g (14.90–19.90 mL/min/100 g) vs. 34.10 mL/min/100 g (33.35–43.17 mL/min/100 g), the grey matter 14.57 mL/min/100 g (13.66–18.72 mL/min/100 g) vs. 32.37 mL/min/100 g (31.03–42.99 mL/min/100 g), the caudal brain 15.47 mL/min/100 g (13.37–21.45 mL/min/100 g) vs. 36.85 mL/min/100 g (32.50–47.18 mL/min/100 g) and the temporal lobe grey matter 18.80 mL/min/100 g (15.89–20.84 mL/min/100 g) vs. 43.32 (36.07–43.58 mL/min/100 g). Median (IQR) hypocapnic cerebrovascular reactivity to CO2 was significantly higher ( P = 0.016) for alfaxalone compared to isoflurane 8.85 %S/mm Hg (6.92–10.44 %S/mm Hg) vs. 3.90 %S/mm Hg (3.80–4.33 %S/mm Hg). Alfaxalone maintained lower cerebral blood flow and higher hypocapnic cerebrovascular reactivity to CO2 than isoflurane. Highlights: Alfaxalone could be an alternative for anesthesia in dogs with intracranial disease. Alfaxalone maintained cerebrovascular reactivity to carbon dioxide. Cerebral blood flow was lower in dogs undergoing alfaxalone anesthesia.